First, rewrite the expression as:
#((2 * 3)(y^2 * y^3 * y))^3 =>#
#(6(y^2 * y^3 * y))^3#
Next, use these rules of exponents to evaluate the #y# terms within the parenthesis:
#a = a^color(red)(1)# and #x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))#
#(6(y^2 * y^3 * y))^3 =>#
#(6(y^color(red)(2) * y^color(blue)(3) * y^color(purple)(1)))^3 =>#
#(6y^(color(red)(2)+color(blue)(3)+color(purple)(1)))^3 =>#
#(6y^6)^3#
Now, use these rules of exponents to complete the evaluation:
#a = a^color(red)(1)# and #(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#
#(6y^6)^3 =>#
#(6^color(red)(1)y^color(red)(6))^color(blue)(3) =>#
#6^(color(red)(1) xx color(blue)(3))y^(color(red)(6) xx color(blue)(3)) =>#
#6^3y^18 =>#
#216y^18#